Peningkatan Hasil Belajar SBK Melalui Metode Pembelajaran Contextual Teaching Learning - Aritonang, Fajar Mangisi (JURNAL PENA EDUKASI, 2018)
Abstract: The purpose of this study is to improve student learning outcomes of class VII-C SMP Negeri 1 Stabat academic year 2017/2018. Intrumen data collector in the form of written test and teacher activation observation sheet in applying Contextual Teaching Learning method (CTL). The results of the study are: (1) In the first cycle found from 32 students of class VII-C obtained 19 people complete learning or about 59.4% and 13 people or about 40.6% unfinished; (2) In the second cycle was found from 32 students of class VII-C obtained 28 people complete learning or about 87.5% and 4 people or about 12.5% unfinished; (3) The result of observation of CTL method implementation by teacher obtained the result in cycle I, the value of 77,38 with the category Skilled enough and in Cycle II, value 92,85 with the category